The labour market and vocational education and training – systems which do not always correspond - Bellmann, Lutz [Verfasser]; Helmrich, Robert [Verfasser] (My University, 2024)
"The labour market and the VET system are characterised by a series of contrary developments. This article focuses on the most important factors in this regard. Following an overview of the main challenges and of current trends, it outlines developments on the labour market and training market and presents the ensuing changes for companies. The authors suggest as two possible solutions the improvement of vocational orientation which supports more young people along the route into VET as well as reforms to initial VET which can help increase the speed of adjustment." (BIBB-Doku)
Keywords: S System beruflicher Bildung; G 2.3.4 Qualifikationswandel; G 1.3.1.1 Ausbildungsstellenmarkt; 370; Beziehung Bildungssystem Beschäftigungssystem; Ausbildungsstellenmarkt; Digitalisierung; Qualifikationsanpassung; Ausbildungsverhalten; Berufsorientierung; Berufsausbildung; Attraktivität